2020
DOI: 10.1371/journal.pone.0232571
|View full text |Cite
|
Sign up to set email alerts
|

Methods to prevent PCR amplification of DNA from non-viable virus were not successful for infectious laryngotracheitis virus

Abstract: Molecular-based testing of poultry dust has been used as a fast, sensitive and specific way to monitor viruses in chicken flocks but it provides no information on viral viability. Differentiation of viable and nonviable virus would expand the usefulness of PCR-based detection. This study tested three treatments (1. DNAse, 2. propidium monoazide [PMA], 3. immunomagnetic separation [IMS]) applied to dust or virus stock prior to nucleic acid extraction for their ability to exclude nonviable virus from PCR amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
(42 reference statements)
3
12
0
Order By: Relevance
“…However, this was not supported by the findings in which infection was unsuccessful with dust or dust extracts collected from infected and clinically sick birds at 3, 7 and 14 dpe and given to 120 susceptible chicks in 6 isolators. This is in agreement with previous report by Bindari et al [ 36 ] that failed to infect cell cultures or chick embryos with qPCR positive dust extracts. These authors also found that spiking dust samples with cultured ILTV reduced the infectivity of the ILTV to chick embryos.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, this was not supported by the findings in which infection was unsuccessful with dust or dust extracts collected from infected and clinically sick birds at 3, 7 and 14 dpe and given to 120 susceptible chicks in 6 isolators. This is in agreement with previous report by Bindari et al [ 36 ] that failed to infect cell cultures or chick embryos with qPCR positive dust extracts. These authors also found that spiking dust samples with cultured ILTV reduced the infectivity of the ILTV to chick embryos.…”
Section: Discussionsupporting
confidence: 94%
“…This is reinforced by experimental demonstration of airborne transmission of field and vaccine ILTV strains, potentially due to infective dust particles in the air [ 24 ]. In contrast, Bindari et al [ 36 ] were unable to isolate ILTV from ILTV PCR positive dust samples in either chick embryos or cell culture. Thus the role of poultry dust in the transmission of ILTV remains unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…These included propidium monoazide and immunomagnetic separation tested on laryngotracheitis virus and ethidium monoazide on avian influenza virus. (11,12) It is worth to report that we also tested on inactivated SARS-CoV-2 suspensions a porcine gastric mucine in situ capture RT-qPCR, a method that was originally implemented in our laboratory for human enteric viruses. (20) Although proper SARS-CoV-2 infectious controls could not be included, those experiments resulted in inconclusive outcomes (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…(10) However, the application of such techniques for enveloped viruses has not fully elucidated as it has failed for avian influenza virus (IAV) and infectious laryngotracheitis virus (ILTV) while it has recently been optimized for porcine epidemic diarrhea coronavirus. (1113) Nonetheless, the implementation of this technique has not been explored for SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dust has also been shown to be useful for the monitoring of pathogens that are primarily transmitted by feather dander such as Marek's disease virus ( Walkden-Brown et al, 2013 ). Respiratory pathogens such as infectious laryngotracheitis virus ( Ahaduzzaman et al, 2019 ), Newcastle disease virus and infectious bronchitis virus ( Tran et al, 2020 ) are detectable in dust samples using PCR although it is not clear whether this represents infective virus from the respiratory tract or inactivated viral nucleic acids present in excreta following passage through the gut ( Bindari et al, 2020 ; Yegoraw et al, 2020 ). It can be expected that pathogens originating in litter material (e.g., litter derived Aspergillus fumigatus ) will also be well represented in dust, however, it should be noted that the proportion of bedding in dust declined to low levels over time as observed in this study.…”
Section: Discussionmentioning
confidence: 99%